Genotypic variability in oil palm (Elaeis guineensis Jacq.) towards drought damages in Benin (West Africa) - ADOUKONOU-SAGBADJA, Hubert (My University, 2019)
Oil palm is an important crop largely produced in the world. However, its productivity is highly impaired by drought in Benin (West Africa). This study aimed at identifing the genotypic diversity in the response to drought conditions among ten oil palm genotypes (L1 to L10) in adult stage based on five predefined drought damage traits: number of green broken leaves (NGBL), number of folded leaves (NFL), number of unopened leaves (NUL) number of base leaves dry out (NBLD) and number of trees with central leaf cabbage toppled (NLCT). Principal component analysis (PCA) has shown that NGBL, NFL and NLCT are more relevant for drought study in adult palms trees. PCA has also shown a high variability in genotypes. Thus, L9, L8, L3, L1, L2 and L10 were drought tolerant whereas L7 was drought sensitive. Between these two groups, L5, L6 and L4 display intermediate tolerance to drought. Planting tolerant genotypes is a necessity to avoid drought damage. Consequently, the future research must insight the biochemical and biomolecular bases of tolerance to drought between the ten genotypes.
Keywords: Oil palm; drought sensitivity; drought damages; drought tolerance